ESTIMATION OF FACTORS EFFECTING VOLUME OF LIVER USING LIVER ANALYSIS SOFTWARE IN COMPUTED TOMOGRAPHY - DOLLY SHARMA; PRIYANKA (International Journal of Pharma and Bio Sciences, 2015)
The aim of the study was to estimate the factors effecting volume of liver. This study included 124 men and 124 women between the ages of 20 and 80 years who came for CT scan of abdomen for various clinical reasons were included in the study. Abdomen Helical protocol was used and raw data was acquired with 5mm slab thickness, incrementation 5mm and it was further reconstructed into 1.5mm. Volume of liver was measured on extended brilliance workspace workstation using liver analysis software. Mann Whitney U test was performed to determine average difference in liver volume between two age groups; 20-50 and 51-80. Result indicated that there was no statistically significant difference between two age groups (p=0.390). Independent sample t test was performed to determine average difference in liver volume between males and females. Result indicated that there was statistically significant difference between gender with respect to liver volume (p<0.001).